Unveiling the Social Dynamics of Religious Conflict in Palembang's House of Worship - Meilano, Donny; Muchtar, Aflatun; Wijaya, Wijaya (Fakultas Dakwah Institut Agama Islam Sunan Giri Ponorogo, 2023)
This research aims to analyze the factors that influenced the conflict over the establishment of the HKBP Church in Talang Kelapa Subdistrict and the role of the government and FKUB in responding to this conflict. This type of research is field research in qualitative form with a case study approach. The data sources used are primary data obtained directly based on field facts, and secondary data sources, namely data collected from various scientific writings, relevant research, and scientific works and books. The data collection method uses observation, in-depth interviews, and documentation. Data analysis uses data reduction, data presentation, and concluding. The research found that the conflict over establishing a house of worship for the HKBP Church occurred due to social, religious, and Local Wisdom factors. Apart from that, there was a conflict in establishing the HKBP Church, because the local community received information that the house of worship would be used as the central or largest house of worship for the HKBP Church in Asia. In order to the local community believes that there is a mission religion in the plan to build a house of worship for the HKBP Church that will be carried out.